(untitled) (CIPEEX, 2025)
The presence of heavy metals in the chemical composition of endodontic sealers and their distribution on the external surface was evaluated. Polyethylene tubes, with an internal diameter and length of 3 mm, were prepared and filled with Sealapex®, Sealer 26®, MTA Fillapex®, Pulp Canal Sealer®, Endofill®, and AH Plus®. The analysis of the presence of heavy metals was performed using energy-dispersive X-ray spectroscopy (EDX). Quantitative measurements in atomic weight percentage (%p) were conducted by two calibrated professionals using the NSS Spectral Analysis System 2.3 software. Element distribution maps on the external surface were obtained by the NetCounts method using the same software. EDX revealed the presence of the following heavy metals: silver (Ag), iron (Fe), nickel (Ni), zinc (Zn), tungsten (W), hafnium (Hf), and zirconium (Zr). The Pulp Canal Sealer® and Endofill® sealers showed high Zn peaks (67.74%p and 63.16%p, respectively). The elements Zr (64.24%p), Hf (1.22%p), and W (26.04%p) were exclusively observed in AH Plus®, while Ag (31.5%p) was detected only in Pulp Canal Sealer®. Traces of Ni were identified in Sealapex® (0.21%p), Pulp Canal Sealer® (0.12%p), and Endofill® (0.10%p). The same was observed for Fe in Sealapex® (0.24%p) and AH Plus® (0.23%p). Heavy metals were poorly identified on the external surfaces. No contaminant heavy metals were observed in the tested sealers.